2022
DOI: 10.1038/s41536-022-00243-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar glutamatergic system impacts spontaneous motor recovery by regulating Gria1 expression

Abstract: Peripheral nerve injury (PNI) often results in spontaneous motor recovery; however, how disrupted cerebellar circuitry affects PNI-associated motor recovery is unknown. Here, we demonstrated disrupted cerebellar circuitry and poor motor recovery in ataxia mice after PNI. This effect was mimicked by deep cerebellar nuclei (DCN) lesion, but not by damaging non-motor area hippocampus. By restoring cerebellar circuitry through DCN stimulation, and reversal of neurotransmitter imbalance using baclofen, ataxia mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…EMG movement‐triggering closed‐loop DBS system has been used to close the loop in essential tremor and performed better than the tremor‐modulated closed‐loop DBS system even though the EMG movement‐triggering system will still trigger stimulation when the patients make movement that do not result in tremor 55 . Motor function depends on the integrity of descending motor pathways that ultimately activate target muscles 31,56 . We recently reported that disruption of cerebellothalamocortical motor circuitry in ataxia mice significantly delays EMG onset and reduces EMG amplitude after electrical or optogenetic DCN stimulation, suggesting an alternation of cerebellar outputs due to the disruption of spinal motor circuits, resulting in reduced motor activity 31 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…EMG movement‐triggering closed‐loop DBS system has been used to close the loop in essential tremor and performed better than the tremor‐modulated closed‐loop DBS system even though the EMG movement‐triggering system will still trigger stimulation when the patients make movement that do not result in tremor 55 . Motor function depends on the integrity of descending motor pathways that ultimately activate target muscles 31,56 . We recently reported that disruption of cerebellothalamocortical motor circuitry in ataxia mice significantly delays EMG onset and reduces EMG amplitude after electrical or optogenetic DCN stimulation, suggesting an alternation of cerebellar outputs due to the disruption of spinal motor circuits, resulting in reduced motor activity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Motor function depends on the integrity of descending motor pathways that ultimately activate target muscles 31,56 . We recently reported that disruption of cerebellothalamocortical motor circuitry in ataxia mice significantly delays EMG onset and reduces EMG amplitude after electrical or optogenetic DCN stimulation, suggesting an alternation of cerebellar outputs due to the disruption of spinal motor circuits, resulting in reduced motor activity 31 . Several clinical reports suggest that chronic muscle denervation is a sign of PD, for which EMG tests play a critical diagnostic role 57,58 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations